Public Perception of the Motives that Lead Political Leaders to Launch Interstate Armed Conflicts: A Structural and Cross-Cultural Study - Mullet, Etienne; EPHE (2013)
The way the people from two culturally very different countries perceive the psychological motives that lead political leaders to launch armed actions against other states was examined. Three types of possible psychological motives, taken from McClelland’s (1985) theory of human motivation, were considered: motives associated with the state’s power (e.g., increasing the country’s economic power), motives associated with other states’ political character (e.g., whether neighboring states are relatively peaceful democracies or threatening autocracies), and motives associated with domestic issues (e.g., appearing as a strong leader able to efficiently fight for the security of the country). A total of 442 participants living in Western Europe (France) and 180 participants living in the Maghreb (Algeria) were presented with a Motives of War questionnaire that was created for the present set of studies. Exploratory and confirmatory analyses showed that the hypothesized model of motives holds with the condition that the increasing power motive is divided into two separate motives: one associated with the economy and one associated with the territory. The motives of war tended to be seen as more personal and as more associated with domestic issues among people living in Algeria than among people living in France. Among traditional/authoritarian people living in France, the motives of war tended to be seen in a more positive light than among liberal people. In contrast, among traditional/authoritarian people living in Algeria, the motives of war tend to be seen in a more negative light than among liberal people.